Factors Affecting Food Choices of Millennials: How they Decide What to Eat? - Shipman, Zehra Dilistan (My University, 2020)
Millennials, who are also known as generation Y, constitute an important group of consumers for the tourism and hospitality industry. Hence, the purpose of this study is to understand which factors affect their food choices and whether these factors show any difference for demographic variables. A quantitative research design using exploratory factor analysis is employed to understand the different dimensions of food choice behavior of millennials. The findings of the study have explored six factors that guide the food purchase of generation Y. In addition, the relative importance of each factor has provided a better understanding of the role of each dimension. Therefore, this study provides implications about how to address the demands of a generation, which could be considered a unique target market for the hospitality industry.